2007
DOI: 10.1038/nchembio0707-360
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the ancient concept of botanical therapeutics

Abstract: Mixtures of interacting compounds produced by plants may provide important combination therapies that simultaneously affect multiple pharmacological targets and provide clinical efficacy beyond the reach of single compound-based drugs. Developing innovative scientific methods for discovery, validation, characterization and standardization of these multicomponent botanical therapeutics is essential to their acceptance into mainstream medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
215
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(227 citation statements)
references
References 29 publications
1
215
1
10
Order By: Relevance
“…One potential advantage of TOM is that the presence of multiple active ingredients or compounds in any one product presents the opportunity to affect multiple targets 5 . Ma et al 25 previously reported 24 verified combinations of TOM compounds, for which mechanisms of action are known.…”
Section: Synergistic Combinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential advantage of TOM is that the presence of multiple active ingredients or compounds in any one product presents the opportunity to affect multiple targets 5 . Ma et al 25 previously reported 24 verified combinations of TOM compounds, for which mechanisms of action are known.…”
Section: Synergistic Combinationsmentioning
confidence: 99%
“…This suggests that the search for TOM-derived compounds with the potential for multitargeting should reach beyond the commercially available natural products. Natural evolution and the greater pool of compounds present in TOMs might have contributed to their similarities with human metabolites being greater than those observed for approved drugs 5,18 . Another explanation is that approved drugs usually go through…”
Section: Synergistic Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the Asian countries, the tradition of utilizing botanicals has a long history [10] and a vision to develop biobased business strategies is one of the main streams of economic development [11,12]. Despite the long history of pyrolysis use, only a limited number of review articles focused on pyrolysis liquids as pesticides or biocides were found.…”
Section: Introductionmentioning
confidence: 99%
“…A number of natural compounds from oriental herbs and plants have been isolated for the treatment of diverse human diseases (1)(2)(3)(4)(5). In particular, a variety of Iris species are potent anti-cancer agents (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%